KEPALA SEKOLAH MENDUKUNG MERDEKA BELAJAR (STUDI KASUS SEKOLAH DASAR) - Putri Shofi; Suwadi Suwadi (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2023)
Abstract This article discusses school principals in supporting independent learning. This article describes the principal in responding to the independent learning program in elementary schools. The principal is a professional official in the school with the task of leading and managing all school resources and working closely with teachers, staff and other employees in educating students to achieve educational goals. The purpose of this study is to examine school principals in implementing independent learning in elementary schools. The method used in this research is the library research method. The results of the study show that the role of the principal in supporting independent learning can be seen from the leadership of the principal, because the leadership of the principal is the key to the success of independent learning. These findings can be used as a reference for implementing independent learning in elementary schools.